THEORITICAL REVIEW: PEMASARAN MEDIA SOSIAL - Rina Sari Qurniawati (Among Makarti, 2018)
Abstract The emerging of social media technology and the popularity of social media sites stem from a simple fact that human beings are social by nature. People are inclined to collect or share information that is important to them. Social media has become one of the most popular marketing channels for many companies, which aims at maximizing their influence by various marketing campaigns conducted from their social accounts on social networks. Social networking sites have become an avenue where retailers can extend their marketing campaigns to a wider range of consumers.  Nowadays, it is practically impossible to formulate marketing strategy without taking social networks into consideration. Adapting some forms of marketing online through social media is a key node for all businesses. The importance of social media lies in its function as the new marketing/promotion platform, which may timely and interactively connect seller and buyers. Business-to consumer or business-to-business reasons use social media in every aspect of their daily life.  Keywords:  Social Media, Marketing, IMC, marketing tools